(untitled) - Sreenivasan Jayashree , Chinnasamy Agamudai Malarvizhi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Industry 4.0 and smart technologies are the most recent development of the manufacturing system that involves an uncertain potential effect on the execution of Industry 4.0 towards attaining sustainability. Therefore, this paper adds to the existing literature by scrutinizing the role of Industry 4.0 technologies on its successful implementation and Triple Bottom Line (TBL) sustainability. A new framework is proposed considering the role of smart technologies that may be played to determine TBL sustainability and effective employment of Industry 4.0 as a mediating variable. As the existing literature did not pay much attention to sustainability from the financial, environmental, and social dimensions while executing Industry 4.0, this study intends to evaluate the links among the variables from the Malaysian perspective. A quantitative analysis will be conducted through a questionnaire-based survey where the SMEs will be the study population. The study intends to strengthen the literature on Industry 4.0, offering a well-structured discussion and a framework on sustainability and smart technologies to produce useful understandings for future research.